POLITIK DAN KEWARGANEGARAAN : PENGALAMAN POLITIK PENYANDANG DISABILITAS TUNA RUNGU DI KOTA PALEMBANG - Ahmad Muksin; Amaliatulwalidain; M.Qur’anul Kariem (Governance, 2024)
This research was conducted to determine the political experiences of deaf people in the city of Palembang. This research uses qualitative methods, which can produce accurate and focused data through interviews and observations. This means that this research is directly involved in the descriptive field which seeks to describe through issues the political experiences of deaf people. This was carried out by researchers at the Gerkatin organization office which is located at Jalan Lieutenant Murod 1, 20 Ilir D.IV, Ilir Timur 1 District, Palembang City, South Sumatra 30128. To see and find out what obstacles are faced by deaf people and to find out about the political experiences of deaf people in general elections. Using Nuri Soeseno's Theory (Republican Citizenship Theory). And Efriza Theory (Political Participation Theory). Based on the results of research and discussions that have been carried out regarding Politics and Citizenship (Case Study of Political Experiences of Deaf People with Disabilities in Palembang City), their political participation still faces a number of obstacles. Deaf people tend to be classified as observers in General Elections, with minimal active involvement in supporting candidates for state office and campaign activities. Inhibiting factors involve a lack of socialization from the KPU, lack of assistance from family or TPS officers, and minimal attention from TPS officers to the special needs of people with disabilities.